2000
DOI: 10.1046/j.1440-1681.2000.03288.x
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmaceutical Considerations In Topical Ocular Drug Delivery

Abstract: 1. Despite the accessibility of the front of the eye, efficient delivery of drug to treat various ocular disorders is a challenge to the formulation scientist. The majority of ophthalmic medications are formulated as eye drops. Due to anatomical constraints, the volume that can be administered is limited to approximately 30 microL. This, together with the efficient clearance system that exists in the front of the eye, makes it difficult to maintain an effective pre-ocular drug concentration for a desired lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(151 citation statements)
references
References 22 publications
1
148
0
2
Order By: Relevance
“…8 Because of these issues, suspension eyedrops are quickly cleared: 90% of the drug is cleared within 2 minutes, and only 5% of the administered dose permeates into the cornea. 9 Nanotechnology has found a place in the medical field by providing new and more efficient ways to deliver treatment. Nanoparticles (NPs), especially biodegradable ones, have also found applications in ophthalmology, by providing safer, less invasive, cheaper treatment options, and by effectively increasing drug concentration in the eyes.…”
Section: Introductionmentioning
confidence: 99%
“…8 Because of these issues, suspension eyedrops are quickly cleared: 90% of the drug is cleared within 2 minutes, and only 5% of the administered dose permeates into the cornea. 9 Nanotechnology has found a place in the medical field by providing new and more efficient ways to deliver treatment. Nanoparticles (NPs), especially biodegradable ones, have also found applications in ophthalmology, by providing safer, less invasive, cheaper treatment options, and by effectively increasing drug concentration in the eyes.…”
Section: Introductionmentioning
confidence: 99%
“…This is due in part to the unique structure of the eye, various application routes, and formulation types that are used for ocular drug delivery. Since it is difficult to collect ocular pharmacokinetic data and data modeling may be difficult, the literature is very limited about ocular pharmacokinetics and mostly covers the measurement of drug levels in aqueous humor following ocular administration (Macha and Mitra 2003;Schoenwald 1990;Mishima 1981;Davies 2000). It is difficult to develop quantitative predictions for interspecies dose adjustments since most of these studies were performed in rabbit eyes with different anatomical and physiological features (such as blinking rate, tear volume, and corneal dimensions) relative to human eyes and because there is little or no data available in human eyes.…”
Section: Pharmacokinetic Considerationsmentioning
confidence: 99%
“…Because of this a significant portion of the applied drug is absorbed through nasolacrimal duct and the mucosal membranes of the nasal, oropharyngeal, and gastrointestinal tract to pass to the system. It has been found that no more than 2% of medication introduced topically to the eye is adsorbed [35][36][37]. Again clinical studies by various workers reveal that the main biological barrier for penetration to the eye is represented by the cornea.…”
Section: Eye-targeted Chemical Delivery Systems (Cdss) and Retrometabmentioning
confidence: 99%